2016
DOI: 10.1016/j.jaci.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes –induced cutaneous lymphocyte antigen–positive T cell–dependent epidermal cell activation triggers T H 17 responses in patients with guttate psoriasis

Abstract: This study reveals a dominant TH17 response of cutaneous lymphocyte antigen-positive T cells activated by epidermal cells and S pyogenes in patients with GP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 51 publications
3
39
0
Order By: Relevance
“…Evidence implicates that GAS-specific Th17 cells are involved in GAS related autoimmune disorders [24]. It is reported that intranasal GAS infection promotes infiltration of GAS-specific Th17 cells into the brain and causes immunopathology in the brain [25].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence implicates that GAS-specific Th17 cells are involved in GAS related autoimmune disorders [24]. It is reported that intranasal GAS infection promotes infiltration of GAS-specific Th17 cells into the brain and causes immunopathology in the brain [25].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, microbial antigens derived from candida or staphylococci preferentially induce Th17 cells . Guttate psoriasis is induced by molecular mimicry after infection with streptococci . Lichen planus is associated with HCV infection …”
Section: Trigger Factors and Early Eventsmentioning
confidence: 99%
“…49 Guttate psoriasis is induced by molecular mimicry after infection with streptococci. 50 Lichen planus is associated with HCV infection. 51 Lessons learned for specific therapy…”
Section: Trigger Factors and Early Eventsmentioning
confidence: 99%
“…Superantigens from GAS have been demonstrated to enhance T cell expression of CLA + , which is a carbohydrate‐moiety expressed by 80% of T cells in the skin, and the abundance of CLA + CD8 + T cells in the blood of patients with psoriasis correlates with disease severity . CLA + T cells in the tonsils and GP lesions of the same patient show identical TCRβ rearrangement (Vβ2 + ), suggesting that migration of these cells occurs from the tonsils to the skin . Once in the skin, the CLA + T cells interact with lesional epidermal cells and induce a dominant Th17 response .…”
Section: Complications Arising From Gas Pharyngitismentioning
confidence: 99%
“…183 CLA + T cells in the tonsils and GP lesions of the same patient show identical TCR rearrangement (V 2 + ), suggesting that migration of these cells occurs from the tonsils to the skin. 184 Once in the skin, the CLA + T cells interact with lesional epidermal cells and induce a dominant Th17 response. 185 Some studies have reported that tonsillectomy results in improvement of psoriasis in the majority of cases and is associated with a reduction in the frequency of skin-homing T cells in the blood that were reactive to peptides derived from human epidermal keratins and streptococcal M proteins.…”
Section: Gpmentioning
confidence: 99%